INTELLECTUAL CAPITAL REPORTING: NEW ACCOUNTING FOR THE NEW ECONOMY - Peter Demediuk , (Asian Academy of Management Journal, 2002)
In the 'new economy', ideas, practices and innovations that arise from the creation of intellectual capital have become a pre-eminent economic resource and the basis for competitive advantage. Attempts to develop cogent accounting praxis that makes intellectual capital discussable and therefore actionable, are constrained by the granular nature of existing definitions and taxonomies of intellectual capital. As a response to this lack of clarity, a model has been proposed that maps how a group of knowledge workers characterise the drivers and outcomes of their human creativity. The model indicates that accounting must break away from the traditional frame of reference that is 'the artifact', 'the entity', 'management control' and 'uniform reporting models'. At issue is whether the same set of measurement tools can provide descriptions of reality that have meaning for the decision making of individuals, and yet provide appropriate resourcing signals, evaluative information, and signs of legitimacy that are required by institutional management and other stakeholders.